COMPARATIVE ANALYSIS OF THE MARKETING PLANS OF XXIIND AND XXIVTH DIAGNOSTICS AND CONSULTANCY CENTRES FOR THE PERIOD FROM YEAR 2016 TO 2018 - Tsvetelina Mihaylova; Desislava Todorova; Tsvetomir Dimitrov; Angel Enchev (Peytchinski Publishing, 2017)
Public healthcare is a field, in which the limited resources must be distributed upon competition between the different necessities of patients and in the setting of rivalry between health care institutions providing medical services. The aim of the study is disclosure of the factors, which influence the state and activity of two healthcare institutions for specialized medical aid in Sofia City. The task of analysis of the marketing plans of two diagnostics and consultancy centre DCCs) was assigned for the period from the year 2016 to 2018. The analysis of the medical and demographic state of the population of Metropolitan Municipality showed that it is necessary efforts to be directed to complete enveloping of the population of up to 18 years of age and above 45 years of age with prophylactic examinations and their enveloping in groups of outpatient registration. The examinations based on outpatient registration were approximately 4% of the total scope of the activity of "DCC XXIInd-Sofia" and about 10% of the total scope of activity of "DCC XXIVth-Sofia". The analysis of the necessities from medical services and the possibilities of their offering showed that the usability of the capacity of XXIVth DCC was 61%, while the usability of the capacity of XXIInd DCC was 91%. The attention of the administration of health care institutions for specialized pre-hospital medical aid must be directed to contractual relations with the firms by voluntary health insurance companies or by the services of occupational medicine.